An analysis of the limnology and sedimentary diatom flora of fourteen lakes and ponds from the Windmill Islands, East Antarctica - Roberts, D; Andrew McMinn; Johnston, N; Gore, DB; Melles, M; Cremer, H (2001)
The limnology and sedimentary diatom flora of fourteen lakes and ponds from the Windmill Islands, East Antarctica, is presented. Saline lakes, saline ponds and freshwater ponds are represented in this data set. The Windmill Island lake diatom flora represents an intermediate floral assemblage between that of the freshwater lakes of the Larsemann Hills and the saline lakes of Vestfold Hills, East Antarctica. Variations within this assemblage are related to water chemistry variables in the Windmill Island lakes. In particular, a lakewater salinity/phosphate gradient can explain the variation observed in the sedimentary diatom flora of the lakes and ponds included in this study.